1999
DOI: 10.1108/00070709910301373
|View full text |Cite
|
Sign up to set email alerts
|

Canonical correlation analysis of customer satisfaction and future purchase of mail‐order speciality food

Abstract: Analyses customer satisfaction with mail‐order speciality foods in the UK and examines the relationship between satisfaction with eight attributes of mail‐order speciality food and their association with overall satisfaction and likelihood of future purchase. Univariate analysis reveals that a high proportion of mail‐order customers experience satisfaction with each of the eight mail‐order attributes, reflected in a high proportion of customers who are satisfied overall and who intend to repurchase the product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 20 publications
2
29
0
1
Order By: Relevance
“…Satisfaction is a delightful degree of post-consumption evaluation or a pleasurable degree of consumption-related fulfillment (Oliver, 1996;Paulssen and Birk, 2007;Ruyter and Bloemer, 1999). Thus, satisfaction is a level of overall pleasure or contentment perceived by a consumer, resulting from the quality of the product or service to fulfill the consumer's expectations, desires, and needs (Mai and Ness, 1999). Based on the above definitions, this study proposed a novel construct, ''green satisfaction,'' and defined it as ''a pleasurable level of consumption-related fulfillment to satisfy a customer's environmental desires, sustainable expectations, and green needs.'…”
Section: Green Marketingmentioning
confidence: 97%
See 1 more Smart Citation
“…Satisfaction is a delightful degree of post-consumption evaluation or a pleasurable degree of consumption-related fulfillment (Oliver, 1996;Paulssen and Birk, 2007;Ruyter and Bloemer, 1999). Thus, satisfaction is a level of overall pleasure or contentment perceived by a consumer, resulting from the quality of the product or service to fulfill the consumer's expectations, desires, and needs (Mai and Ness, 1999). Based on the above definitions, this study proposed a novel construct, ''green satisfaction,'' and defined it as ''a pleasurable level of consumption-related fulfillment to satisfy a customer's environmental desires, sustainable expectations, and green needs.'…”
Section: Green Marketingmentioning
confidence: 97%
“…Customer satisfaction is one of the most widely discussed topics in the marketing field (Oliver, 1996). For example, previous studies have demonstrated customer satisfaction can lead to consumer's purchase intentions (Mai and Ness, 1999;Martenson, 2007), and repeat purchase behavior (Chang and Tu, 2005). Consumers who are highly satisfied with a brand may recall its name directly, compared to consumers who are less satisfied with it.…”
Section: Green Marketingmentioning
confidence: 99%
“…A further development extends the satisfactionloyalty relationship to include profitability. When high levels of satisfaction matches or exceeds customers' expectations, the future purchase intension is confirmed (Mai and Ness 1999). Loyalty enhances profitability through an increase in the scale and scope of the relationship with loyal customers, lower customers recruitment costs, reduced customer price sensitivity and lower customer servicing costs (Hallowell 1996).…”
Section: Research Objectivesmentioning
confidence: 97%
“…In the face of competitive market conditions, businesses need to deliver consumer value by engaging customers in long term relationships in order to increase chances of re-purchase (Mai & Ness, 2006). The intention to re-purchase is a post purchase behavioural intention that influences customer loyalty, complaint and switch intentions (Meng, Liang & Yang, 2011).…”
Section: Customer Intention To Re-purchasementioning
confidence: 99%